Central Bank Digital Currencies: Current Challenges in Latin America - Mata Hernández, José Miguel; Castillo Escamilla, María Yezenia (Universidad Francisco de Paula Santander, 2025)
In response to the recommendation from the Bank for International Settlements to central banks in various economies to develop their own Central Bank Digital Currency (CBDC), some central banks in Latin America are developing their own CBDC, aiming to be a payment method used by the population instead of cryptocurrencies and stablecoins. This research conducts a comparative analysis of the current landscape and challenges in the development and implementation of CBDCs in Latin America. Additionally, a hypothesis test using the T-student method is employed to analyze whether the rise in the use of cryptocurrencies could affect the adoption of CBDCs. Similarly, a dynamic SWOT matrix is used to present the strengths, weaknesses, opportunities, and threats of already launched CBDC projects. According to the results obtained, it is demonstrated that CBDC projects in Latin America are still in the research stage, but some have been canceled. Furthermore, only Brazil and Uruguay have advanced projects. However, there are challenges and issues for implementation and use by the population, among which the increase in the use of cryptocurrencies and stablecoins stands out.